2011
DOI: 10.1007/s10290-011-0100-3
|View full text |Cite
|
Sign up to set email alerts
|

The costs of moving money across borders and the volume of capital flight: the case of Russia and other CIS countries

Abstract: Capital flight, Illicit money flows, Financial sector liberalization, Russia, Commonwealth of Independent States, E26, F31, F32, P33, P37,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…On the other hand, in the seven countries of the Commonwealth of Independent States (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005), the liberalization of the trade and financial sectors accelerated capital flight by making capital easier to transfer abroad. In the short-term, strengthening supervision rather than liberalization of the external sector seems more likely to combat capital flight (Brada, Kutan, and Vukšić, 2011). However, financial liberalization policies by themselves may not help reduce the capital flight of 21 emerging market economies from 1980 to 2004 (Yalta & Yalta, 2012).…”
Section: Determinants Of Capital Flightmentioning
confidence: 99%
“…On the other hand, in the seven countries of the Commonwealth of Independent States (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005), the liberalization of the trade and financial sectors accelerated capital flight by making capital easier to transfer abroad. In the short-term, strengthening supervision rather than liberalization of the external sector seems more likely to combat capital flight (Brada, Kutan, and Vukšić, 2011). However, financial liberalization policies by themselves may not help reduce the capital flight of 21 emerging market economies from 1980 to 2004 (Yalta & Yalta, 2012).…”
Section: Determinants Of Capital Flightmentioning
confidence: 99%
“…Many studies have been conducted on the relationship between capital flight and macroeconomic variables. Studies such as those by Brada (2011) and Hoa and Lin (2016) found a negative relationship between capital flight and macroeconomic variables, while Aderoju (2017), Saheed and Ayodeji (2012), and Uguru et al, (2014) found a positive relationship. Although most of the reviewed studies focused on the impact of capital flight on economic growth, the effects of capital flight on economic development have not been considered.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, autocratic countries can implement economic regulation to control the effects of individual stock prices and profits in these securities by lax insider trading laws (Eckard, 2005). For outflows, Brada et al (2011, p. 741) conclude that “government repression and regulation … [are] more effective in combating capital flight” in the Commonwealth of Independent States (CIS) countries. This conclusion is in line with Ghosh (2016), who suggests that autocratic regimes use capital controls to deter money from leaving.…”
Section: Related Literature and Hypothesesmentioning
confidence: 99%